The simulation of mode coupling during ELM crash by using BOUT++ - Y. H. Zhu; T. Y. Xia; J. Huang (AIP Advances)
The edge localized mode (ELM), which poses potential threats to divertor plates and first wall, is critical to understand in magnetic confinement fusion devices such as tokamaks. The BOUT++ framework serves as one of the most widely used models for ELM simulations. This study investigates mode-coupling effects during ELM crashes through simulations employing different torus cases within BOUT++. Furthermore, using a three-wave coupling method, it examines the evolution of the dominant toroidal modes during ELM crashes. A key finding reveals that the mode that obtains the most energy will be the dominant mode in the subsequent period. In addition, by applying the three-wave coupling method in a 1/3 torus, the research analyzes energy transfer between low-n and high-n modes during the first ELM crash. The low-n mode (n = 3) is found to decrease ELM size, while the high-n modes increase ELM size in this simulation.